Myeloperoxidase Inhibition in Heart Failure With Preserved or Mildly Reduced Ejection Fraction: SATELLITE Trial Results - Lam Carylon S.P.; Lund Lars H; Sham Sanjuv J; Voors Andriaana A. Erlinge David; Saraste Antti; Pirazzi Carlo; Gorve Erik L; Barasa Anders; Schou Morten; Aziz Ahmed; Svedlund Sara; Van Wijngaarden Jan; et al. (Elsevier B.V., 2025)
Background
Inflammation is a key driver of heart failure with preserved left ventricular ejection fraction. AZD4831 inhibits extracellular myeloperoxidase, decreases inflammation, and improves microvascular function in preclinical disease models.
Methods and Results
In this double-blind phase 2a study (Safety and Tolerability Study of AZD4831 in Patients With Heart Failure [SATELLITE]; NCT03756285), patients with symptomatic heart failure, left ventricular ejection fraction of ≥40%, and elevated B-type natriuretic peptides were randomized 2:1 to once-daily oral AZD4831 5 mg or placebo for 90 days. We aimed to assess target engagement (primary end point: myeloperoxidase specific activity) and safety of AZD4831. Owing to coronavirus disease 2019, the study was terminated early after randomizing 41 patients (median age 74.0 years, 53.7% male). Myeloperoxidase activity was decreased by more than 50% from baseline to day 30 and day 90 in the AZD4831 group, with a placebo-adjusted decreased of 75% (95% confidence interval, 48, 88, nominal P < .001). No improvements were noted in secondary or exploratory end points, apart from a trend in Kansas City Cardiomyopathy Questionnaire overall summary score. No deaths or treatment-related serious adverse events occurred. AZD4831 treatment-related adverse events were generalized maculopapular rash, pruritus, and diarrhea (all n = 1).
Conclusions
AZD4831 inhibited myeloperoxidase and was well tolerated in patients with heart failure and left ventricular ejection fraction of 40% or greater. Efficacy findings were exploratory owing to early termination, but warrant further clinical investigation of AZD4831.